Call of the wraith / 4 - Sands, Kevin (Sands, Kevin. Blackthorn key adventure, 2018)
Christopher Rowe is shipwrecked in Devonshire, where children are disappearing and a ghost is suspected, but even Tom and Sally's arrival may not cure his amnesia in time to help.